Impact of Surface Nano-textured Stainless Steel Prepared by Focused Ion Beam on Endothelial Cell Growth - Nazneen, F.; Schmidt, M.; McLoughlin, E.; Petkov, N.; Herzog, G.; Arrigan, Damien; Galvin, P. (American Scientific Publishers, 2013)
The modification of stent surfaces with nano-structures has the potential for limiting late stent restenosis. We report here the patterning of 316L austentitic stainless steel with arrays of nano-pits of two nominal diameters: 120 and 180 nm. These nano-textured surfaces were prepared by focused ion beam milling. The influence of the ion beam current on the nano-features was investigated by scanning electron and atomic force microscopies. The optimum ion beam currents were 280 pA for 120 nm nano-pits and 920 pA for 180 nm nano-pits. The depths of the nano-pits formed were (65±24) nm (120 nm) and (84±36) nm (180 nm). This wide distribution of the depths is due to the polycrystalline nature of 316 L stainless steel, which has a strong influence on the milling rates. Endothelial cells were grown in vitro on these substrates for 1, 3 and 5 days. The cells were viable for the duration of the cell culture on the nano-textured substrates. There was no significant difference in the adhesion and the proliferation based on the nano-pit diameter.